A PV FED Three Phase Switched Z-source Multi Level Inverter for Induction Motor Drives - Sinu KJ; G. Ranganathan (Institute of Advanced Engineering and Science, 2018)
Generally induction motor drives posses higher harmonic contents in line voltage and current due to high switching frequency used in inverters. Conventional induction motor drives employ two level voltage source inverters which has THD in level of 50%. This paper presents a switched z-source multilevel inverter which has voltage boosting capability and has lesser THD level in comparison with conventional two level voltage source inverters. This drive is fed from a photo voltaic source because of its voltage boosting capability. A single phase five level switched z-source inverter is initially designed and considered as single cell and three such cells are created for powering three phase induction motor. The proposed three cell PV source switched z-source multilevel inverter for three phase induction motor is simulated in MATLAB/Simulink software to verify merits of proposed IM drive